Wireless Mobile Sensor Network for the System Identification of a Space Frame Bridge - Zhu, Dapeng; Guo, Jiajie; Cho, Chunhee; Wang, Yang; Lee, Kok-Meng (IEEE/ASME transactions on mechatronics, 2012)
This research investigates the field performance of flexure-based mobile sensing nodes (FMSNs) developed for system identification and condition monitoring of civil structures. Each FMSN consists of a tetherless magnetic wall-climbing robot capable of navigating on steel structures, measuring structural vibrations, processing measurement data, and wirelessly communicating information. The flexible body design of the FMSN allows it to negotiate with sharp corners on a structure, and attach/detach an accelerometer onto/from structural surface. Our previous research investigated the performance of the FMSNs through laboratory experiments. The FMSNs were deployed to identify minor structural damage, illustrating a high sensitivity in damage detection enabled by flexible mobile deployment. This paper investigates the field performance of the FMSNs with a pedestrian bridge on the Georgia Tech campus. Multiple FMSNs navigate to different sections of the steel bridge and measure structural vibrations at high spatial resolution. Using data collected by a small number of FMSNs, detailed modal characteristics of the bridge are identified. A finite element (FE) model for the bridge is constructed. The FE model is updated based on the modal characteristics extracted from the FMSN data.